2022
DOI: 10.1371/journal.pone.0268627
|View full text |Cite
|
Sign up to set email alerts
|

“I always find myself very tired and exhausted”: The physical impact of caring; a descriptive phenomenological study of the experiences of prostate cancer caregivers in Cape Coast, Ghana

Abstract: Introduction Prostate cancer is a significant public health burden and a significant cause of morbidity and mortality among men worldwide. This study, therefore, explored how caring affects the physical health of family caregivers of prostate cancer patients. Method The study adopted a descriptive phenomenological method. Twelve participants were recruited using the purposive sampling technique. A semi-structured face to face, in-depth interviews were conducted with family caregivers of patients living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…The wives of men in this study with genitourinary and GIT cancers reported having reduced their sexual desire. These findings depart from a findings of the phenomenological study conducted in Ghana by Owoo et al [ 31 ] about spouses of prostate cancer patients who did not report about reduced sexual desires. LeSeure and Chongkham-Ang [ 14 ] agree that the findings of their systematic review indicated that caregivers adapted to the fact that the patients with cancer were not able to adequately perform sexual functions.…”
Section: Discussioncontrasting
confidence: 99%
“…The wives of men in this study with genitourinary and GIT cancers reported having reduced their sexual desire. These findings depart from a findings of the phenomenological study conducted in Ghana by Owoo et al [ 31 ] about spouses of prostate cancer patients who did not report about reduced sexual desires. LeSeure and Chongkham-Ang [ 14 ] agree that the findings of their systematic review indicated that caregivers adapted to the fact that the patients with cancer were not able to adequately perform sexual functions.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, participants also reported difficulties related to weakness, fatigue, rib injury, swelling in the feet, and herniated discs. It was found in related research that carers deal with physical difficulties and pains [14,[24][25][26]. It was also determined in previous research that caregivers frequently experience fatigue [26,27].…”
Section: Discussionmentioning
confidence: 95%
“…It was found in related research that carers deal with physical difficulties and pains [14,[24][25][26]. It was also determined in previous research that caregivers frequently experience fatigue [26,27]. Another difficulty experienced by caregivers is sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic activities of daily living (9,11,21,25,35,40,41,48,54,64,66,68) Activities done by caregivers (20 studies) Instrumental activities of daily living (9,11,21,25,35,36,(40)(41)(42)(46)(47)(48)53,54,59,(62)(63)(64)66,68) Relationship between the caregiver and the patient (21,48) Motivation to become an ICG Level of responsibility the caregiver has over the patient (11,25,45,48,64) Positive impact of caregiving on ICGs (41,59) Economic impact of caregiving 1. Cost of caregiving (9,25,36,40,48,…”
Section: Sub-heading Studiesmentioning
confidence: 99%